Systematic literature review on which maternal alcohol behaviours are related to fetal alcohol spectrum disorders (FASD). Issue 12 (19th December 2018) - Roozen, Sylvia; Peters, Gjalt-Jorn Ygram; Kok, Gerjo; Townend, David; Nijhuis, Jan; Koek, Ger; Curfs, Leopold
Abstract : Objectives: Fetal alcohol spectrum disorders (FASD) is a worldwide problem. Maternal alcohol consumption is an important risk factor for FASD. It remains unknown which alcohol consumption patterns most strongly predict FASD. The objective of this study was to identify these. Design: Systematic literature review. Methods: We searched in PubMed, PsychINFO, PsycARTICLES, ERIC, CINAHL, Embase and MEDLINE up to August 2018. The query consisted of keywords and their synonyms related to FASD, pregnancy and behaviour. Studies were excluded when not published in English, were reviews or involved non-human subjects. Substantial heterogeneity precluded aggregation or meta-analysis of the data. Instead, data were qualitatively inspected. Results: In total, 21 studies were eligible for further data analysis. All studies that measured both maternal alcohol drinking behaviours and FASD reported retrospective data on maternal drinking patterns, employing both continuous and categorical measures and exhibiting substantial heterogeneity in measures of alcohol consumption (eg, timing of exposure, quantification of alcohol measure and definition of a standard drink). Study quality improved over time and appeared higher for studies based on active case ascertainment, especially when conducted in schools and when behaviour was assessed through interviews. Conclusions: We aimed to identify specific maternal drinking behaviour(s) related to FASD. The state of the literature precludes such conclusions. Evidence-based preventive measures necessitate identifying which prenatal alcohol drinking behaviour(s) are most in need of intervention. Therefore, we formulate three recommendations for future research. First, future studies can optimise the value of the collected dataset through specifying measurements and reporting of maternal drinking behaviours and avoiding categorised measures (nominal or ordinal) whenever possible. Second, samples should not be selected based on FASD status, but instead, FASD status as well as maternal alcohol consumption should both be measured in a general population sample. Finally, we provide 10 reporting guidelines for FASD research.